Pemberdayaan Masyarakat melalui Inisiatif Pengadaan “Keranjang Sedekah Sampah” dan “Budidaya Maggot” untuk Pelestarian Lingkungan - Widyasari, Sindy; Muallidin, Isnaini; Fitriyani, Rifka Sukma; Yuniarto , Adam Anderson; Prayogo, Muchamad Imron; Putri, Della Nadia; Laresatu, Al Gibran Bintang; Pawitra, Hafizh Sina; Puspandari, Aulia Denova Candra Putri; Hakiim, Naufal; Karunia, Diyah (ASOSIASI IDEBAHASA KEPRI, 2025)
This community empowerment activity aims to increase awareness and involvement of youth and mothers in systematic waste management, as well as to realize a structured waste management strategy through the